2008
DOI: 10.1029/2008jc004932
|View full text |Cite
|
Sign up to set email alerts
|

On the solitary wave paradigm for tsunamis

Abstract: [1] Since the 1970s, solitary waves have commonly been used to model tsunamis especially in experimental and mathematical studies. Unfortunately, the link to geophysical scales is not well established, and in this work, we question the geophysical relevance of this paradigm. In part 1, we simulate the evolution of initial rectangular-shaped humps of water propagating large distances over a constant depth. The objective is to clarify under which circumstances the front of the wave can develop into an undular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
204
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(221 citation statements)
references
References 65 publications
10
204
1
2
Order By: Relevance
“…Such a configuration is relevant to the modelling of the near-shore tsunami propagation (see e.g. Madsen et al (2008), Tissier et al (2011) and references therein) but is also of a broader significance in the context of the general description of the dispersive shock wave propagation in weakly inhomogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…Such a configuration is relevant to the modelling of the near-shore tsunami propagation (see e.g. Madsen et al (2008), Tissier et al (2011) and references therein) but is also of a broader significance in the context of the general description of the dispersive shock wave propagation in weakly inhomogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this will emphasise the important role of the undular bore solutions of the KdV equation, as seen in some tsunami observations and numerical simulations, see Arcas and Segur (2012) and Grue et al (2008) for instance. It is pertinent to note here that the critique of the validity of KdV models by Madsen et al (2008), Madsen and Schaffer (2010) and Arcas and Segur (2012), amongst others, is based on solitary wave dynamics, and we suggest that this is an overly restrictive view of the value of KdV models.…”
Section: Introductionmentioning
confidence: 70%
“…This indicates inter alia that the nonlinear and dispersive effects contained in the KdV model can indeed develop over plausible distances when applied as here to the near shore region. In much deeper water, where say h 0 ¼ 1:6 km; ¼ 0:02 for an initial amplitude of again 1 m, the corresponding length scale x s h 0 À1 ¼ 2760 km; 80 times larger, indicating inapplicability of a KdV model, as argued in a different manner by Madsen et al (2008), Madsen and Schaffer (2010) and Arcas and Segur (2012) for instance.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, new insights provided by Constantin and Johnson, 17 Constantin, 18 and Madsen et al, 19 had seriously questioned the paradigm of describing tsunamis as the solitary waves or N-waves. They demonstrated that initial surface displacement induced by submarine earthquakes is highly relative to the seismic activities, and the time-and space-scales of geophysical tsunamis are typically orders of magnitude different from the scales embedded in the classical Korteweg-deVries (KdV) tie between the dispersion and the nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that initial surface displacement induced by submarine earthquakes is highly relative to the seismic activities, and the time-and space-scales of geophysical tsunamis are typically orders of magnitude different from the scales embedded in the classical Korteweg-deVries (KdV) tie between the dispersion and the nonlinearity. Madsen et al 19 indicated that the bulk of the tsunami is very poorly represented by the solitary waves, and the front of the tsunami hardly ever develops into the solitary waves. Constantin 18 discussed the relevance of soliton theory to the modeling of tsunamis in the context of the real tsunamis records.…”
Section: Introductionmentioning
confidence: 99%